The Impact of the Question-and-Answer Method on Learning Outcomes in Elementary Civic Education (PKn): A Systematic Literature Review - Sulistio, Indriyati; Arrahim, Arrahim; Dermawan, Deden Dicky (Yayasan Sembilan Pemuda Indonesia, 2025)
In elementary PKn Education, traditional teacher-centered approaches often limit student engagement and hinder learning outcomes. To address this, interactive teaching strategies such as the Question-and-Answer (Q&A) method have gained attention for their potential to enhance conceptual understanding and student participation. This study aims to systematically review existing literature to evaluate the impact of the Q&A method on student learning outcomes in elementary PKn Education classes. Using a quantitative approach within the framework of a Systematic Literature Review (SLR), the research analyses relevant studies that explore the application of the Q&A method in primary school PKn Education. The review focuses on student engagement, conceptual understanding, and academic performance. The findings reveal that the Q&A method significantly enhances student involvement, supports deeper understanding of PKn concepts, and leads to improved academic achievement. The method fosters a more dynamic and participatory classroom environment, which positively affects learning outcomes. This systematic review highlights the effectiveness of the Q&A method as a student-centred instructional strategy in PKn Education at the elementary level. It underscores the need for educators to adopt interactive teaching techniques to improve student learning, and provides a foundation for future research and practice in the field.